Mitigasi Risiko: Seruan Boikot Terhadap Perusahaan Yang Terafiliasi Dengan Israel - Sri Apriani, Endang; Agustin, Kety Lulu; Endang Sri Apriani (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
This research aims to prove that the issue of boycotts has an influence on the population of issuers in the Non-Primary Consumer Goods Sector. using purposive sampling techniques, the characteristics raised were companies that were suspected of being affiliated with Israel. From these characteristics, 4 samples were obtained which were then analyzed using SPSS tools. The collected trading and volatility data were tested using the Wilcoxon Test. This test compares 2 paired data to determine whether there are differences between the 2 data. It can be seen from the results of the normality test that the data is not normally distributed. The results of this research show that there are differences in volatility before the boycott call and after the boycott call for UNVR, MAPI and MAPB. Meanwhile, regarding stock trading profits, the 4 research objects, namely UNVR, MAPI, MAPB, and FAST, have no differences despite calls for a boycott. However, seeing the market response with differences in volatility when calls appear, researchers suggest waiting and seeing the stock market situation until it is more conducive.